Carrier Screening, Hematological Indices, and Iron Chelation Practices in Extended Families of Thalassemia Major in a Subset of Karachi - Ghazal Irfan, Saima Manzoor, Kiran Khan, Aftab Hussain Abro, Munazza Rashid, Muhammad Aitmaud Uddolah Khan (Pakistan Journal of Medical & Health Sciences, 2024)
Background: In Pakistan especially Karachi where consanguinity maintains high carrier rates within extended family’s beta-thalassemia major poses a significant genetic burden. Transfusion-dependent patient outcomes are compromised by inadequate iron chelation adherence and family-based detection is still underutilized despite the availability of screening technologies. The carrier frequency hematological indices and chelation practices of relatives visiting a nearby thalassemia center were evaluated in this study. Methodology: At Thalassemia Center Karachi 200 extended family members (first- to third-degree relatives) of 50 transfusion-dependent beta-thalassemia major index cases were included in a cross-sectional study. Participants underwent peripheral smears HPLC for HbA2/F confirmation complete blood counts and structured interviews after giving their informed consent. Microcytic cases were evaluated based on iron status (ferritin). Chelation information taken from case files in the index. Group comparison and descriptive statistics were used to analyze the data. Results: The carrier frequency was 34% (68/200) with siblings and cousins having the highest rates at 44.8% and 38.9 % respectively. Microcytosis was seen in carriers (MCV 66. 8±5. 2 fL MCH 21. 1±2. 1 pg p < 0.001 vs non-carriers). Of the microcytic subjects 30% were iron-deficient and 55% were carriers. Chelating coverage was 92% but only 48% of patients had good adherence deferasirox accounted for 54% of cases. 71% of respondents reported consanguinity and 32% reported using premarital screening. Conclusion: Extended family screening resolves iron deficiency overlap by producing high carrier detection with distinct hematological discrimination. Inadequate chelation adherence highlights gaps in monitoring. Keywords: Career screening, hematological indices, iron chelation thalassemia major, Karachi